Enterocolitis Is a Risk Factor for Bowel Perforation in Neonates With Hirschsprung's Disease: A Retrospective Multicenter Study - Zhu, Tianqi; Zhang, Guofeng; Meng, Xinyao; Yang, Jixin; Niu, Yonghua; He, Ying; Yang, Heying; Xiong, Xiaofeng; Feng, Jiexiong (Frontiers in Pediatrics, 2022)
Background and aim: We evaluated the clinical features of neonatal Hirschsprung’s disease (HSCR)-associated bowel perforation (perforated HSCR) and investigated risk factors related to it. Methods: We retrospectively collected clinical data of neonates (<1 month of age) with perforated HSCR from multicenters in China from January 2006 to December 2019. A total of 142 patients (6.7%) with perforated HSCR were enrolled in the study. A 1:2 matching method was used to compare the clinical information of HSCR patients with and without bowel perforation during the neonatal period. The risk factors for bowel perforation were identified using univariate and multivariate logistic risk regression analyses. Results: Perforation site was present in the proximal ganglionic bowel in 101 (71.1%) cases and the distal aganglionosis segment in 41 (28.9%) cases. Adjacent marginal tissue from the perforated intestine revealed varying degrees of inflammatory cell infiltration, and the severity of enterocolitis was higher in the proximal ganglionic bowel than in the distal aganglionosis segment (p < 0.05). In the univariable and multivariable logistic analyses, clinical symptoms, such as vomiting (adjusted OR = 2.06, 95% CI: 2.01–2.88, p < 0.05), and inflammation index in hematologic tests, such as neutrophil proportion (adjusted OR = 1.09, 95% CI: 1.05–1.33, p < 0.05) and CRP (adjusted OR = 2.13, 95% CI: 1.01–3.27, p < 0.05) were associated with increased risk for perforated HSCR. Conclusion: Clinical Hirschsprung disease-associated enterocolitis (HAEC) highly correlated with perforated HSCR. Timely treatment of HAEC should be appropriate therapeutic approaches to prevent perforated HSCR.